Evaluation of toxicity using zebrafish embryo model and preparation of enteric-coated pellets containing Panax notoginseng saponins - Khanh Van Nguyen, Nhung Thi Hong Nguyen, Hoa Thi Dinh, Hanh Thi Hong Vu, Thi Thu Giang Vu (Journal of Applied Pharmaceutical Science, 2024)
Panax notoginseng saponins (PNS) extracted from the root of Panax notoginseng (Burk.) F. H. Chen are the main biologically active substances. However, PNS have low permeability and degradation in the acid gastric environment, leading to their limited bioavailability. This study aimed to determine the acute toxicity of PNS in zebrafish larvae and prepare enteric-coated pellets of PNS to enhance their permeability and stability. The survival proportion, the morphological abnormalities, and the heartbeat of zebrafish embryos were performed at treated doses of PNS ranging from 0.01 to 50 μg/ml. Administration of PNS at doses greater than 10 μg/ml may result significantly in morphological alterations such as pericardial edema and curved tail. The core pellets containing PNS, polyethylene glycols, and absorption enhancers were fabricated by the dripping method. Then, the dripping pellets were coated using Eudragit L100 as an enteric coating polymer. The characterizations of core pellets and enteric-coated pellets were evaluated. The produced dripping pellets showed advantageous features, such as ease of preparation, excellent uniformity, notable friability, high dissolution rate, and good stability. In addition, absorption enhancers were successfully incorporated into the core pellets to improve the permeability of PNS. Differential scanning calorimetry, X-ray powder diffraction, and Fourier-transform infrared spectroscopy profiles revealed that the drug was maintained in an amorphous state and did not interact with the excipients during the pellet preparation process. Histological evaluation showed that dripping pellets caused a minor effect on the surface of the jejunal mucosa. The enteric-coated pellets displayed smooth surface morphology, desirable sphericity, good flowability, uniform content, and stability in an acidic pH 1.2 environment and rapid drug release in a pH 6.8 buffer solution. Based on the findings, the enteric-coated pellets may improve the absorption and stability of PNS.
Keywords: Panax notoginseng saponins, dripping pellet, enteric-coated pellet, absorption enhancers, zebrafish larvae